Prototype Setup Hardware Choice for the DUCK System - Dmitriy Beznosko; Valeriy Aseykin; Alexander Dyshkant; Alexander Iakovlev; Oleg Krivosheev; Tatiana Krivosheev; Vladimir Shiltsev; Valeriy Zhukov (Quantum Beam Science)
This article covers the overall design hardware choices for the prototyping activities for the DUCK (Detector system of Unusual Cosmic ray casKades). The primary goal of the DUCK system is to verify the existence of the unusual cosmic events reported by other collaborations and to look at the possibilities of adding innovations to the EAS (Extensive Atmospheric Shower) analysis methods of the EAS disk measurements at the observation level. Additionally, design and construction of the system provide educational experience to the students involved in the project and are developing the research capabilities of the university campus. The prototyping process has helped to choose between various design solutions in the process of optimizing of the individual detector components.